2020
DOI: 10.1136/jitc-2020-001326
|View full text |Cite
|
Sign up to set email alerts
|

Lack of myeloid cell infiltration as an acquired resistance strategy to immunotherapy

Abstract: BackgroundImmunotherapy of cancer is successful but tumor regression often is incomplete and followed by escape. Understanding the mechanisms underlying this acquired resistance will aid the development of more effective treatments.MethodsWe exploited a mouse model where tumor-specific therapeutic vaccination results in tumor regression, followed by local recurrence and resistance. In depth studies on systemic, local and tumor intrinsic changes were performed with flow and mass cytometry, immunohistochemistry,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 49 publications
2
17
0
Order By: Relevance
“…33 Therapy failure due to an inadequate intratumoral macrophage response, despite the presence of fully activated intratumoral tumor-specific CD8 + T cells, fits with earlier reports demonstrating that macrophages are required for TC-1 tumor regression after therapeutic vaccination 14 26 and functions as a secondary immune escape mechanism. 34 Notably, while these effects were most prominently demonstrated in the context of high levels of tumor-produced IL-6, similar observations were made in the TC-1 control tumor model, which produced much lower levels of IL-6. We previously showed that IL-6 production by tumors altered the function of spontaneously tumor-infiltrating DCs and macrophages, reflected by a lower expression of MHC class II by these myeloid cell subsets.…”
Section: Discussionsupporting
confidence: 59%
“…33 Therapy failure due to an inadequate intratumoral macrophage response, despite the presence of fully activated intratumoral tumor-specific CD8 + T cells, fits with earlier reports demonstrating that macrophages are required for TC-1 tumor regression after therapeutic vaccination 14 26 and functions as a secondary immune escape mechanism. 34 Notably, while these effects were most prominently demonstrated in the context of high levels of tumor-produced IL-6, similar observations were made in the TC-1 control tumor model, which produced much lower levels of IL-6. We previously showed that IL-6 production by tumors altered the function of spontaneously tumor-infiltrating DCs and macrophages, reflected by a lower expression of MHC class II by these myeloid cell subsets.…”
Section: Discussionsupporting
confidence: 59%
“…Interestingly, NPs also induced the infiltration of neutrophils in the untreated tumor ( Supplementary Materials Figure S6A ). The levels of mature (CD86 + ) and inflammatory (Ly6C high ) myeloid cells have recently been shown to increase in treatment-responsive tumors but not in relapsed tumors that display resistance to treatment [ 62 ]. In line with this, we observed an increase in the levels of mature inflammatory myeloid cells and a decrease in non-inflammatory (Ly6C − ) cells in the treated tumor after treatment with the combination, compared to all other treatments ( Figure 6 A).…”
Section: Resultsmentioning
confidence: 99%
“…Tumour microenvironment is determined by crosstalk between different signalling pathways taking place in cancer cells, immune cells, and other cancer-associated cells such as fibroblasts [ 96 , 136 , 137 , 138 , 139 , 140 , 141 , 142 , 143 ].…”
Section: Tumour-promoting Inflammation and Evading Immune Destructionmentioning
confidence: 99%